2005
DOI: 10.1089/tmj.2005.11.20
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of a Care Coordination-Enhanced Telehome Care Program for Elderly Veterans with Chronic Heart Failure

Abstract: Veterans with chronic heart failure (HF) are frequently elderly, have numerous comorbid chronic medical illnesses, frequent hospitalizations, and have high rates of cardiovascular events. Within the Veterans Health Administration (VHA), primary care providers are required to manage the majority of HF patients because access to cardiac specialty care within the VHA may be limited. We designed and implemented a care-coordinated, nurse-directed home telehealth management program for veterans with difficult-to-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 17 publications
2
62
0
1
Order By: Relevance
“…Prior studies have found that use of the HBP was associated with greater compliance with prescription medications, 13 titration of medications, 14 and compliance with nonpharmacologic recommendations, 15 suggesting the HBP likely improved both care delivery and patient self-management, which may have contributed to reductions in mortality and hospitalization observed in the present study. In addition, secondary analyses of multiple randomized trials have shown improved outcomes in patients who demonstrate high pharmacologic adherence in the placebo arm comparable to those receiving the study drug, supporting the possibility that patient engagement may be a marker for other beneficial characteristics.…”
Section: Discussionsupporting
confidence: 51%
“…Prior studies have found that use of the HBP was associated with greater compliance with prescription medications, 13 titration of medications, 14 and compliance with nonpharmacologic recommendations, 15 suggesting the HBP likely improved both care delivery and patient self-management, which may have contributed to reductions in mortality and hospitalization observed in the present study. In addition, secondary analyses of multiple randomized trials have shown improved outcomes in patients who demonstrate high pharmacologic adherence in the placebo arm comparable to those receiving the study drug, supporting the possibility that patient engagement may be a marker for other beneficial characteristics.…”
Section: Discussionsupporting
confidence: 51%
“…This finding is consistent with other reports in 1) cardiac rehabilitation in the home [10], suggesting that ECG telemonitoring was only useful to enroll higher risk patients, whereas all others could obtain the same results with a simple telephone connection during the training session and 2) a randomized trial for home telecare in congestive heart failure [11] where the reduction of readmissions was similar for a group with telephone care and other with televisits and telemonitoring. A recently reported elderly telemonitoring program based on a simple question and answer device [12] also supports this view. In COPD, according to our study team's opinion, a telephonic-, internet-, or WAP-based symptoms questionnaire, as also reported by some researchers [13], [14], might be more useful than spirometry and pulse-oximetry telemonitoring, or may complement the information they provide, that is, similar to what is done in the field of diabetes, which is a pioneer in telemedicine for chronic care.…”
Section: Discussionmentioning
confidence: 62%
“…All these professionals share the WPMM and use it as a collaborative working tool (schedule specialist or home visits, send messages to other professionals, view visit agenda). Other home telemedicine systems are either directed only to primary care and case managers [12], integrate specialists in a marginal way (faxing occasional reports) [3], or are addressed only to specialists [4], [15]. Care coordination is understood to have a crucial role in chronic patient care and allows adapting the level of care received by each patient to his/her needs at each moment and a smooth transfer among levels when required (exacerbations).…”
Section: Discussionmentioning
confidence: 99%
“…Home-based case management directed by a nurse in conjunction with TM-case managed telemedicine (CMTM) is an effective intervention for enhancing the continuum of care (Speedie et al, 2008). It has been shown to improve outcomes in those patients classified as high risk, in elderly veterans (Schofield, 2005), patients with chronic atrial fibrillation (Inglis et al, 2004), and diabetics (Chumbler et al, 2005). CMTM has also shown reduce cost of care, improve compliance, self-efficacy and patient education.…”
Section: In Home Healthcare Settingsmentioning
confidence: 99%